Проблема пошуку і впровадження сучасних інтерактивних технологій як принцип ефективності реформування освіти під час ведення активних бойових дій - Оніщенко, Тетяна Євгенівна; Корнієнко, Олена Олександрівна; Рябоконь, Олена Вячеславівна; Саліонов, Володимир Олександрович; Onishchenko, T. Ye.; Kornienko, O. O.; Ryabokon, O. V.; Salionov, V. O. (My University, 2025)
The article substantiates the expediency of searching for and implementing modern educational technologies, taking into account their effectiveness and efficiency in reforming education against the background of active hostilities. The relevance of this problem lies in the fact that the trend of ‘life-long learning’ as ‘lifelong learning’ is opposed to the traditional ‘lifelong learning’ and involves the continuous development of personal effectiveness of today's students, and educational technologies, methods and techniques are designed to provide them with constant access to learning and prepare future professionals to be competitive and proactive in the VUCA world. The use of modern educational tools through the principle of interactivity changes the logic of the educational process (learning does not take place from theory to practice, but from the formation of new experience to its theoretical understanding through application), which meets the requirements of considering several interactive technologies: problem-based learning, organisation of project and research activities, digital technologies, contextual learning, game technologies, technologies for the formation of 4K (critical and creative thinking, cooperation and communication). The potential of interactive educational tools will ensure that future specialists achieve the educational outcomes in demand in the 21st century, develop ‘flexible’ competences, and professional competitiveness.
The problem of finding and implementing modern interactive technologies as a principle of effective education reform during active hostilities
Keywords: innovative educational technologies; modern interactive technologies; problem-based learning technologies; contextual learning technologies; technology for organising project and research activities; 4K forming technologies; digital technologies; game technologies